Building serverless architectures with Microsoft Azure : design scalable applications and microservices that effortlessly adapt to the requirements of your customers - Bass, Daniel (Packt Publishing, 2018)
Migrating your application to a cloud-based serverless architecture doesn't have to be difficult. Reduce complexity and minimize the time you spend administering servers or worrying about availability with this comprehensive guide to serverless applications on Azure. Key Features Provides information on integration of Azure products Plan and implement your own serverless backend to meet tried-and-true development standards Includes step-by-step instructions to help you navigate advanced concepts and application integrations Book Description Many businesses are rapidly adopting a microservices-first approach to development, driven by the availability of new commercial services like Azure Functions and AWS Lambda. In this book, we'll show you how to quickly get up and running with your own serverless development on Microsoft Azure. We start by working through a single function, and work towards integration with other Azure services like App Insights and Cosmos DB to handle common user requirements like analytics and highly performant distributed storage. We finish up by providing you with the context you need to get started on a larger project of your own choosing, leaving you equipped with everything you need to migrate to a cloud-first serverless solution. What you will learn Identify the key advantages and disadvantages of serverless development Build a fully-functioning serverless application and utilize a wide variety of Azure services Create, deploy, and manage your own Azure Functions in the cloud Implement core design principles for writing effective serverless code Who this book is for This book is ideal for back-end developers or engineers who want a quick hands-on introduction to developing serverless applications within the Microsoft ecosystem.